A rule-driven approach for architectural self adaptation in collaborative activities using graph grammars. (7th May 2010) - Bouassida Rodriguez, Ismael; Drira, Khalil; Chassot, Christophe; Guennoun, Karim; , Mohamed Jmaiel
Architectural adaptation is important for handling self-configuring properties of autonomic distributed systems. It can be achieved by model-based management of dynamic architectures. Describing dynamic architectures includes defining rules for reconfiguration management. Within this research context, several works have been conducted using formal specification to handle this complexity. Graph and graph rewriting-based approaches showed, through many studies, their appropriateness to tackle architectural adaptation problems. However, scalability of such approaches remains an open issue and has been rarely explored. In this paper, we investigate this issue. We introduce a graph-based general approach for handling of dynamic architectures and we illustrate it within a scenario of collaboration support in crisis management systems. We elaborate the formal models for dynamic architecture management. Using the French Grid GRID5000, we conducted an experimental study to assess the scalability of the elaborated models.